2020
DOI: 10.1002/ece3.6072
|View full text |Cite
|
Sign up to set email alerts
|

Critical transitions in rainfall manipulation experiments on grasslands

Abstract: As a result of climate and land‐use changes, grasslands have been subjected to intensifying drought regimes. Extreme droughts could interfere in the positive feedbacks between grasses and soil water content, pushing grasslands across critical thresholds of productivity and leading them to collapse. If this happens, systems may show hysteresis and costly management interventions might be necessary to restore predrought productivity. Thus, neglecting critical transitions may lead to mismanagement of grasslands a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
(93 reference statements)
1
9
0
Order By: Relevance
“…Although in our experiment the total biomass in Control plots increased with increasing rainfall, it was never higher than in the RR plots, even in the wettest year. Other authors (Wilcox et al, 2017;Matos et al, 2020) considered that the relationship between rainfall and productivity is complex, with productivity saturating at high rainfall, and this appears to be shown by our results.…”
Section: Rainfall and Biomass Productionsupporting
confidence: 83%
“…Although in our experiment the total biomass in Control plots increased with increasing rainfall, it was never higher than in the RR plots, even in the wettest year. Other authors (Wilcox et al, 2017;Matos et al, 2020) considered that the relationship between rainfall and productivity is complex, with productivity saturating at high rainfall, and this appears to be shown by our results.…”
Section: Rainfall and Biomass Productionsupporting
confidence: 83%
“…In grasslands, there is a positive feedback between grasses and soil water content (Matos et al, 2020). A continuous grass layer reduces evaporation and run-off of water, therefore soil water content increases; this leads to better vegetation growth.…”
Section: Rainfall and Biomass Productionmentioning
confidence: 99%
“…In our experiment, the reduced rainfall values were within the range of rainfall values recorded over the last one hundred years. Several authors have suggested that well-established grassland communities are already adapted to environmental stress (Grime et al, 2008;Matos et al, 2020); because, for rainfall, long-term trends are smaller than interannual variations.…”
Section: How Well Did the Experiments Achieve Its Aim?mentioning
confidence: 99%
“…Although, studies of grasslands in United States found productivity to be strongly correlated with annual precipitation (Knapp and Smith, 2001), other meta-analyses investigating the effects of drought or reduced rainfall on grassland productivity that included studies from a wider geographical area (Beier at al., 2012;Ward et al, 2016) have found considerable heterogeneity in the responses of grasslands to reduced rainfall. Many studies in these reviews are from semiarid environments (Knapp and Smith, 2001;Beier at al., 2012;Wilcox et al, 2017), with relatively few studies in regions where annual rainfall is unlikely to limit productivity (Matos et al, 2020). Other studies of United Kingdom grasslands have shown that reducing summer rainfall has little effect on biomass production over periods of a few years (Grime et al, 2000;Fry et al, 2014).…”
Section: Rainfall and Biomass Productionmentioning
confidence: 99%